Molecular Characterization and Phylogenetic Profiling of Methicillin-Resistant Staphylococcus aureus from Poultry Meat in Nagpur - Bhatkar, Sujata Gajanan; Warke, Shubhangi Rambhau; Tikoo , Mehak Ramesh (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Antimicrobial resistance (AMR) represents a danger to public health, and a “One Health” strategy taking into account the reservoirs in humans, animals and the environment is need of the hour. The present study was designed to investigate the prevalence of Methicillin resistant Staphylococcus aureus in poultry meat to establish genetic relationships among the MRSA isolates. In the present study, out of 50 samples of poultry meat, 19 (38%) were detected by conventional methods to be S. aureus, and 15 (30%) were confirmed by molecular detection of nuc gene. A prevalence of 9/19 (47.36%), 11/19 (57.89%), 16/19 (84.21%), 13/19 (68.42%), 9/19 (47.36%) and 6/19 (31.57%) resistance was observed in S. aureus isolates by phenotypic testing against Methicillin, Gentamicin, Penicillin-G, Tetracycline, Azithromycin and Vancomycin respectively, while as the mecA gene was detected in 56% (5/9) of the isolates that exhibited methicillin resistance. The sequencing and phylogenetic analysis of mecA gene of the representative positive samples revealed that the sequence of the isolate exhibited (98.52% and 98.88%) similarity with the human (Homo sapiens) sequences of Iraq and Egypt. The results of our study imply that the current management practices utilized in the poultry sector may be the cause of the increased prevalence and spread of antimicrobial-resistant bacteria in their environment.